Legal Protection of Inpatients in Clinic in Improving Complete Health Services - Novel Habibi; Anwar, Dicky Andrian; Odang Suparman (Research Horizon, 2025)
Legal protection in healthcare services is a crucial component in ensuring patients’ rights are upheld, particularly in primary inpatient clinics where the potential for medical error still exists. A lack of understanding regarding legal procedures and complaint mechanisms can hinder the realization of patients’ rights. The aim of this study is to examine the legal protection afforded to patients at the Shofa Gondangrejo Inpatient Primary Clinic, the legal remedies available when patients suffer losses due to unfulfilled rights, efforts to improve comprehensive health services, and how these services are supported by legal protection. This study employs a normative juridical method using primary and secondary data, with data collection conducted through interviews and questionnaires with the clinic’s public relations team. The findings suggest that legal protection is relatively well implemented, particularly through informed consent procedures prior to medical action. Legal efforts include mediation and possible legal action under Articles 1365 and 1366 of the Civil Code. Comprehensive service improvement is achieved through enhancing staff competence, fostering a patient-centred culture, promoting effective communication, and strengthening governance. The study concludes that patient rights and obligations must be regulated, and structured complaint procedures must be established to optimize legal protection in healthcare settings.